Long term observations of Aristeus antennatus: Size-structures of the fished stock and growth parameters, with some remarks about the 'recruitment' - Orsi Relini L.; Relini G. (Dynamique des populations marines, 1998)
A brief history of the attempts that have been made to derive growth parameters for A. antennatus is given. Length-frequency distributions are often incomplete, given that the locations of shrimps change with age and, apparently, also with geographical factors, a fact that is reflected in the available growth estimates. Initially the life span was taken to be short, while in the most recent studies it is estimated to be 4-5 years. In summer 1987, a very abundant group of small individuals appeared in the Gulf of Genoa. The growth of these 'recruits' was followed up over a period of three years and a growth rate of about 5 mm CL per year was recorded. The validated segment of life points to maximum life span of about 10 years. A comparison of the size-structures of the fished stock before and after the 1987 'recruitment' makes it possible to discuss the recruitment in A. antennatus, making inferences about the migratory abilities of the red shrimp. The 1987 recruits ranged in size from 20 to 44 mm CL and were almost all spawners. The 1988 peak of catches and the evolution of the size-structure in the following years with decreasing numbers of the youngest shrimps may represent the first biological evidence of long-term cycles in the population, which are reflected in the fluctuating success of the fishery.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)